Importance-Performance Matrix Analysis (IPMA) of intellectual capital and Islamic work ethics in Malaysian SMEs - Mat Zin, Sakinah; Che Mat, Rosfatihah; Abd Manaf, Khamisah (Universiti Teknologi MARA, Kelantan, 2018)
This study used Al-Ghazali’s Economic Theory and Ibn Khaldun’s Theory of Development as the theoretical underpinning to examine the business performance. Six factors (human capital, organizational capital, relational capital, spiritual capital and Islamic work ethics) were identified to model their impact on SME business performance in Malaysia. Survey questions from prior studies were adopted and customized to collect data. A total of 445 entrepreneurs responded to the survey. Partial least Square (PLS) SmartPLS 3.2.6 was used for data analysis. The results of the study revealed that human capital, organizational capital, technological capital and Islamic work ethics significantly influenced business performance. Further to that the authors conducted an Importance-Performance matrix analysis to determine priority variables to focus on for the implications to entrepreneurs.